Effect of racial bias on composite construction. Issue 3 (23rd March 2020) - Bhardwaj, Kavya; Hole, Graham
Summary: We investigated how prior bias about a face's racial characteristics can affect its encoding and resultant facial composite construction. In total, 61 participants (24 Europeans, 18 Indians living in India and 19 Indians living in Europe) saw a racially ambiguous unfamiliar face and were led to believe it was either European or Indian. They created a composite of this face, using EFIT6. Two groups of independent raters (one Indian, the other European) then assessed the apparent race of each composite. A different two groups (one Indian, one European) assessed each composite's degree of resemblance to the target face, to determine whether this was influenced by the constructors' initial categorisation of the target face as "own‐race" or "other‐race." Composites appeared significantly more "Asian" or "European" according to the bias induced in their creators, but there was no evidence of any own‐race bias in the resemblance ratings for the composites.